Management of information security - Whitman, Michael E. (Thomson Course Technology, 2008)
Updated to maintain the industry currency and academic relevance, Management of Information Security continues to provide an overview of information security from a management perspective, as well as a thorough understanding of the administration of information security. Written by two Certified Information Systems Security Professionals (CISSP), this book has the added credibility of incorporating the CISSP Common Body of Knowledge (CBK), especially in the area of information security management.